Social Skills and School Coexistence - Santos-Muñoz, Zonia E. (2023)
Considering that social skills have been poorly managed in students due to various factors such as dysfunctional homes, lack of economy that often forces parents to leave their minor children in the care of relatives or people outside the family family, who are not interested in the formation of children's social skills. Another relevant factor is the media, which mostly broadcast programming with high rates of violence, generating stereotypes that influence behavior. These situations are not only confined to the home space, but are reflected in the educational institution, where interaction with other children generates socialization conflicts, causing a worrying school coexistence, where educational actors face conflicting situations that break the normal environment. that it must be tolerant and free of violence. In accordance with the above, it allows us to highlight the importance of this research to try to determine the relationship between social skills and school coexistence in basic education students.